In search of the 'great horse': A zooarchaeological assessment of horses from England (AD 300–1650). (7th September 2021) - Ameen, Carly; Benkert, Helene; Fraser, Tamsyn; Gordon, Rebecca; Holmes, Matilda; Johnson, Will; Lauritsen, Malene; Maltby, Mark; Rapp, Karina; Townend, Tess; Baker, Gary Paul; Jones, Laura May; et al.
Abstract: Popular culture presents a deep‐rooted perception of medieval warhorses as massive and powerful mounts, but medieval textual and iconographic evidence remains highly debated. Furthermore, identifying warhorses in the zooarchaeological record is challenging due to both a paucity of horse remains relative to other domesticates, and the tendency of researchers to focus on osteological size, which makes it difficult to reconstruct in‐life usage of horses and activity related changes. This paper presents the largest zooarchaeological dataset of English horse bones ( n  = 1964) from 171 unique archaeological sites dating between AD 300 and 1650. Using this dataset alongside a modern comparative sample of known equids ( n  = 490), we examine trends in size and shape to explore how the skeletal conformation of horses changed through time and reflected their domestic, elite and military roles. In addition to evidencing the generally small stature of medieval horses relative to both earlier and later periods, we demonstrate the importance of accurately exploring the shape of skeletal elements to describe the morphological characteristics of domestic animals. Furthermore, we highlight the need to examine shape variation in the context of entheseal changes and biomechanics to address questions of functional morphology and detect possible markers of artificial selection on past horses.